Genetic diversity and cluster analysis of local pigmented rice from East and North Kalimantan, Indonesia based on quantitative and qualitative characters - HAMIDAH HAMIDAH; WIDI SUNARYO; RUSDIANSYAH RUSDIANSYAH; NURHASANAH NURHASANAH (Society for Indonesian Biodiversity, 2024)
Abstract. Hamidah, Sunaryo W, Rusdiansyah, Nurhasanah. 2024. Genetic diversity and cluster analysis of local pigmented rice from East and North Kalimantan, Indonesia based on quantitative and qualitative characters. Biodiversitas 25: 1938-1945. Pigmented rice is a functional food containing antioxidants and various essential nutrients that are very beneficial for health. The substantial advantages of pigmented rice encourage the importance of research activities in exploring pigmented rice germplasms and further identifying unique and valuable traits for the development of superior rice varieties. This research aims to evaluate genetic diversity of pigmented rice based on quantitative and qualitative characters and examine their genetic relationship for future pigmented rice improvement strategies. Fifteen pigmented rice from East and North Kalimantan, Indonesia were used in this study. Nine quantitative and ten qualitative traits were observed and used to identify the genetic diversity of pigmented rice cultivars. The data then were used to group the pigmented rice based on their similarity degree using cluster analysis to form a phylogenetic tree hierarchically in a dendrogram. The results showed that there were large genetic differences based on quantitative and qualitative characters in the pigmented rice, showing a high genetic diversity either in brown or black rice cultivars. Based on the genetic relationships analysis, the fifteen pigmented rice cultivars were clustered in four groups with genetic similarity of ?90%. The genetic diversity and relationship in this study emphasize the crucial of revealing the genetic identity of local pigmented rice from East and North Kalimantan.